GTX-11 attenuates lung fibrosis, inflammation and vascular remodeling in preclinical models of lung fibrotic disease - Montes-Worboys, Ana; Milara, Javier; Farrera, Consol; Fernández-Asensio, Cristina; Sánchez-Díez, Silvia; Mercadé, Jaume; Montero, Paula; Roger, Inés; Molina-Molina, María; Ruiz-Cánovas, Eugènia; Cortijo, Julio (Frontiers in Pharmacology, 2026)
BackgroundFibrotic interstitial lung diseases (ILDs) are characterized by different degrees of inflammation and fibrosis of the lung parenchyma that are associated with progressive loss of breath, high morbidity and mortality. Current therapeutic options are limited, so there remains a significant need for effective and well-tolerated treatments. GTX-11 is an orally available small molecule in development for the treatment of fibrotic diseases. In this study, we aimed to assess the therapeutic potential of GTX-11 in different preclinical models of lung fibrotic disease.MethodsWe assessed the activity of GTX-11 and its active metabolite, GTX-11m, in the bleomycin-induced pulmonary fibrosis model and in vitro in primary fibroblast cell cultures, including human normal lung fibroblasts (hNLFs) and ILD patient-derived fibroblasts.ResultsIn the murine model, GTX-11 treatment improved animal survival and significantly reduced lung fibrosis as measured by Ashcroft score and collagen deposition. GTX-11 also reduced the inflammatory cell count in bronchoalveolar lavage fluid and pro-inflammatory factors in lung tissue. Additionally, GTX-11 significantly improved lung vascular dysfunction and reduced pulmonary vascular remodeling. The preclinical anti-fibrotic effects of GTX-11 were comparable to, or in some cases exceeded, those of currently approved anti-fibrotic drugs used in clinical practice. In vitro, GTX-11m demonstrated anti-fibrotic and anti-inflammatory activity in hNLFs and ILD patient-derived fibroblasts. GTX-11m inhibited TGFβ-induced expression of key fibrotic markers and reduced fibroblast-to-myofibroblast transition and inflammatory cytokine production. The effects were consistent across the different tested ILD cultures and resulted from the prevention of SMAD2 and SMAD3 activation by TGFβ. The GTX‐11m anti-fibrotic and anti-inflammatory effects were comparable or better than nintedanib.ConclusionAltogether, our studies reveal that GTX-11 is an effective antifibrotic both in vivo and in vitro, suggesting that GTX-11 has potential as a therapeutic option for fibrotic ILDs.